On Pulsatile Hydromagnetic Flow of an Oldroyd Fluid With Heat Transfer - SRINIVAS, S.; MALATHY, T.; SACHDEV, P. L. (Engineering Transactions, 2014)
The problem of heat transfer to pulsatile flow of hydromagnetic viscoelastic fluid has been studied. Expressions for the velocity, temperature distribution and mass flow rate are obtained. The rate of heat transfer at the plates has also been calculated. These expressions are evaluated numerically for various values of the parameters. The influence of pertinent parameters on temperature, heat transfer coefficient and mass flux has been studied and numerical results obtained are presented graphically.